Turmeric (Curcuma longa L.): new application as source of fiber and antioxidants in pasta with whole wheat flour (2018)
The demand of healthy foods for preventing non-communicable diseases has increased, and developments include ingredients with health effects, such as whole grain wheat and turmeric. Both areadded in the present study as source of fiber and antioxidants in pasta. This work aimed to evaluate the effect of the addition of turmeric flour in pasta containing whole grain wheat flour and refined wheat flour on its fiber content, and technological and antioxidant properties. For this, there were made three controlpastas with grain wheat flour ranging between 600 and 700 g kg-1. Additionally, seven turmeric pastas were prepared according to a linear experimental design (22), with three central points. Technological analyses included cooking test, color and texture measurement. A Principal Components Analysis was performed for selecting two formulations for further proximate and antioxidant capacities tests. The selected formulations were CP3 (70 WGF: 30 RWF) and TP3 (5 g TF, 60 WGF: 40 RWF), which presented similar technological properties and high average dietary fiber (74.3 g kg-1 ). TP3 presented the highest total phenolics content (534.46 ± 1.93 mg kg-1), DPPH• (5.70 ± 0.10 g kg-1 of Trolox Equivalent (TE), and ABTS (9.02 ± 0.58 g kg-1 of TE), with high retention of antioxidant capacity after cooking. TF promoted the color modification in pastas with WGF, accentuating yellow color, while keeping the cooking properties; it is therefore a natural ingredient that confers color and phenolic compounds in products containing WGF.